2019
DOI: 10.3390/cli7100119
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Green Infrastructures in Urban Planning for Climate Change Adaptation

Abstract: The population that lives in cities has surpassed the one that lives in the countryside. Cities are recognized as apriority source of pollution. The degradation of air quality and the phenomenon of Urban Heat Island (UHI) are some of the most well-known consequences of urban development. The adaptation of the cities is emerging as one of the greatest challenges that urban planners will face in this century. Urban Green Infrastructures (GIs) could help cities adapt to climate change, and the strategy of expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 51 publications
0
61
0
13
Order By: Relevance
“…The way we, in the post-pandemic world, rethink and reshape access to green infrastructure will be the greatest test of urban resilience [92]. As urban populations increase, cities globally need to provide new, accessible and multifunctional green infrastructure as a conscious investment in the health of its citizens and resilience against future environmental change and challenges [93,94]. As of today, exposure to parks and recreation grounds often is beneficial to the health of those living in gentrified or gentrifying neighbourhoods.…”
Section: Discussionmentioning
confidence: 99%
“…The way we, in the post-pandemic world, rethink and reshape access to green infrastructure will be the greatest test of urban resilience [92]. As urban populations increase, cities globally need to provide new, accessible and multifunctional green infrastructure as a conscious investment in the health of its citizens and resilience against future environmental change and challenges [93,94]. As of today, exposure to parks and recreation grounds often is beneficial to the health of those living in gentrified or gentrifying neighbourhoods.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that when the rough sets theory is applied to the conservation of resources in Etna Park, the model used provides an excellent eco-eco tool (ecological-economic) [48,54,55] for decision-makers where the application of multi-disciplinary contributions [56] is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of roof retrofitting depends on: the structural static capacity of the buildings, the cover material and the physical aspects of the roof, such as the available surface and inclination [28]. In addition, the local built environment plays a significant role in urban areas, due to the shadowing effects of the surrounding buildings [29].…”
Section: Roofs Analysis and Classificationmentioning
confidence: 99%